OKINAWA : THE LAST NAVAL BATTLE OF WW2 : THE OFFICIAL ADMIRALTY ACCOUNT OF OPERATION ICEBERG - Grehan, John (Great Britain : FRONTLINE BOOKS, an imprint of Pen & Sword Books Ltd., 2022)
"Having all but swept the Japanese Imperial Navy from the vast expanse of the Pacific Ocean, the Allied forces stood on the brink of invading the Japanese Home Islands. The launching pad for the invasion was to be the island of Okinawa. Amid the terrible slaughter and the shocking casualty statistics of the U.S. Tenth Army and the U.S. Marines, as well as the unrelenting defiance of the Japanese defenders so often detailed in the many books on the battle, the vital part played by the Allied navies in transporting, landing, and supporting the ground offensive is all too often overlooked. The naval forces involved included the U.S. Task Force 58 and the British Pacific Fleet composed of ships from the Royal Australian Navy, the Royal Canadian Navy, and the Royal New Zealand Navy which together with those of the Royal Navy constituted the most powerful fleet Britain had ever put together. The total firepower of the Allied force was staggering, consisting of 18 battleships, 27 cruisers, 177 destroyers/destroyer escorts, 11 fleet carriers, 6 light carriers and 22 escort carriers and various support and troop transport ships. Pitted against this formidable array was the Japanese Combined Fleet, with just one super battleship, one light cruiser and eight destroyers. But the Japanese had one other fearful weapon - the kamikaze. The resultant battle saw the Japanese fleet wiped out, but the Allies lost twenty-four support vessels and a further 386 ships were damaged - many at the hands of the kamikaze pilots. After the fighting the Admiralty called for a summary of the battle to be written for internal Royal Navy consumption. It is that secret report, which it was never intended would be seen by the public, that is published here for the first time"--Publisher's description
Includes index
Keywords: Military operations, Naval; World War, -- 1939-1945 -- Campaigns -- Japan -- Okinawa Island; Okinawa Island (Japan) -- History